Paul Poiret e o diálogo entre moda e arte: a sintonia com as mudanças sociais e do pensamento entre o final do século XIX e a década de 1930 - Lima, Natália Dias de Casado (2019)
The French Belle Époque was a period that took place between the end of the 19th century and 1914 and, during those years, the capital of France, Paris, had several infrastructural, technological and basic sanitation changes. The city was embellished and new types of leisures, ended up influencing new social activities and even the greater possibility of amusements at night with gas lighting followed by the electric. Meanwhile, an artistic aesthetic called Art Nouveau also appeared, being reproduced in objects, architecture and even in clothes. It was also in this period that the first department stores began to appear, as well as the haute couture houses. The most sought-after dressmakers were seen practically as "celebrities", while some of them struggled to attain "artist" status. Among these famous dressmaker was Paul Poiret, the central object of this research. He was an adept in the Art Nouveau style and was quite influential among his peers, but despite launching several inspiring tendencies and even being considered by some as one of the pioneers of the Art Deco style, Poiret didn’t show indifference to other modern tendencies, passing through your creations in the fashion world and visual arts. Your business didn’t survive the prêt-à-porter changes in the industry, gradually lost fame after the First World War. In order to understand the fall and bankruptcy of this couturier and artists, it was necessary to speak about the cyclical movement of fashion, the course of ideas in the postwar period and how this influenced society and fashion, coming to the conclusion that all of those things and financial problems, private problems and aesthetic choices of Poiret, that always acted more like an artist than a fashion businessman, which may also have caused the fall of this couturier. Due to these reasons, this research is based on the themes of fashion, art, "trend" and renewal, involving the name of Paul Poiret and the change of the start of the XX century’ssociety thinking, using references for the methodology books like The symbolic power (1992), by Pierre Bourdieu, and Rites of Spring (1991), by Modris Eksteins. To talk about Poiret himself, his autobiography, King of fashion (2009), were used, and Couture Culture (2003), by Nancy Troy, besides many books and articles that also helped the construction of this dissertation.